PENGARUH DIAMETER PIPA SALURAN GAS BUANG TIPE STRAIGHT THROW MUFFLER TERHADAP UNJUK KERJA MOTOR BENSIN EMPAT LANGKAH - Sanata, Andi (ROTOR, 2011)
Exhaust muffler system is commonly called is one vital part of a motor vehicle. This serves as an exhaust silencer is removed from the machine until at a certain noise level permitted with little possibility of a decline in torque and engine power. This study aims to determine the influence of the exhaust pipe diameter of straight throw gasoline engine performance, pressure, exhaust gas flow rate and intensity of noise generated. From the results of research in getting that throw straight exhaust pipe diameter which was able to improve gasoline engine performance, pressure, flow rate of exhaust gas and noise intensity. This is evident from the results of research that shows that there was an increase by using a exhaust pipe diameters greater straight throw. Keywords: exhaust pipe, exhaust silencer and straight throw